Structural Breaks, Cointegration, and Causality by VECM Analysis of Crude Oil and Food Price - Pala, Aynur (International Journal of Energy Economics and Policy, 2013)
This papers investigated form of the linkage beetwen crude oil price index and food price index, using Johansen Cointegration test, and Granger Causality by VECM. Empirical results for monthly data from 1990:01 to 2011:08 indicated that evidence for breaks after 2008:08 and 2008:11. We find a clear long-run relationship between these series for the full and sub sample. Cointegration regression coefficient is negative at the 1990:01-2008:08 time period, but adversely positive at the 2008:11-2011:08 time period. This results represent that relation between crude oil and food price chanced. Keywords: Crude oil price; food price; structural break; VECM JEL Classifications: C32; Q10; Q40